Thermal and hydrodynamic performance analysis of circular microchannel heat exchanger utilizing nanofluids - Mohammed, H.A.; Bhaskaran, G.; Shuaib, N.H.; Abu-Mulaweh, H.I.; Saidur, Rahman (Emerald, 2012)
Purpose - The purpose of this paper is to investigate numerically the thermal and hydrodynamics performance of circular microchannel heat exchanger (CMCHE) using various nanofluids. Design/methodology/approach - The three-dimensional steady, laminar developing flow and conjugate heat transfer governing equations of a balanced MCHE are solved using finite volume method. Findings - The results are shown in terms of temperature profile, heat transfer coefficient, pressure drop, wall shear stress, pumping power, effectiveness and performance index. The addition of nanoparticles increased the heat transfer rate of the base fluids. The temperature profiles of the fluids have revealed that higher average bulk temperatures were obtained by the nanofluids compared to water. The addition of nanoparticles also increased the pressure drop along the channels slightly. The increase in nanoparticle concentrations yielded better heat transfer rate while the increase in Reynolds number decreased the heat transfer rate. Research limitations/implications - The tested nanofluids are Ag, Al 2O 3, CuO, SiO 2, and TiO 2. Reynolds number range varied from 100 to 800 and the nanoparticle concentration varied from 2 per cent to 10 per cent. Practical implications - Parallel flow in CMCHEs is used in thermal engineering applications and the design and performance analysis of these CMCHE are of practical importance. Originality/value - This paper provides the details of the thermal and hydrodynamics performance analysis of flow heat exchangers using nanofluids, which can be used for heat transfer augmentation in thermal design.